Staged Endovascular Treatment for Peripheral Arterial Disease with Arteriovenous Fistula and Venous Insufficiency - Yamanoha, Tatsushi; Suzuki, Kazuhiko; Ko, Yoshihiro; Hoshina, Toshiyuki; Shimizu, Shogo (Japanese Journal of Vascular Surgery, 2022)
We performed staged endovascular treatment for a rare case with comorbid peripheral arterial disease, arteriovenous fistula, and venous insufficiency in the leg. A 79-year-old man presented with pain, bulging veins, and skin pigmentation in the left leg. Computed tomography revealed a long occlusion of the left femoral artery and arteriovenous fistulas between the peroneal artery and the great saphenous vein. Although the ankle brachial pressure index was normalized, the left leg symptoms and skin perfusion pressure did not improve after endovascular treatment for the femoral artery due to blood stealing to the great saphenous vein and venous insufficiency through micro arteriovenous fistulas. Therefore, we underwent full length closure of the great saphenous vein using cyanoacrylate closure (CAC) and coil embolization for the residual arteriovenous fistula. Subsequently, the patient’s symptoms rapidly disappeared and the circulation in the leg improved. Staged arteriovenous endovascular treatment may be effective in cases of complex vascular disease, as in this case. In particular, CAC may be a useful treatment for micro arteriovenous fistulas that mainly return to the saphenous vein.